Cryptic diversity in Black rats Rattus rattus of the Galápagos Islands, Ecuador. Issue 11 (5th May 2016) - Willows‐Munro, Sandi; Dowler, Robert C.; Jarcho, Michael R.; Phillips, Reese B.; Snell, Howard L.; Wilbert, Tammy R.; Edwards, Cody W.
Abstract: Human activity has facilitated the introduction of a number of alien mammal species to the Galápagos Archipelago. Understanding the phylogeographic history and population genetics of invasive species on the Archipelago is an important step in predicting future spread and designing effective management strategies. In this study, we describe the invasion pathway of Rattus rattus across the Galápagos using microsatellite data, coupled with historical knowledge. Microsatellite genotypes were generated for 581 R. rattus sampled from 15 islands in the archipelago. The genetic data suggest that there are at least three genetic lineages of R. rattus present on the Galápagos Islands. The spatial distributions of these lineages correspond to the main centers of human settlement in the archipelago. There was limited admixture among these three lineages, and these finding coupled with low rates of gene flow among island populations suggests that interisland movement of R. rattus is rare. The low migration among islands recorded for the species will have a positive impact on future eradication efforts. Abstract : Few if any of the world's ecosystems are free from invasion and the unique habitats of islands are particularly at risk. Understanding the phylogeographic history and population genetics of invasive rodents on the Galápagos Archipelago is an important step in predicting future spread and designing effective management strategies. In this study the invasion pathways of the invasive rodent Rattus Rattus across the Galápagos Archipelago is clarified using microsatellite data, coupled with historical knowledge. We demonstrate that patterns of historical human colonization have shaped the introduction and spread of invasive rodents to these islands.